Relationality and theories of the gaze: an analysis of the black female body archetype in the work of contemporary African artists - Friar, Taylor (Michaelis School of Fine Art, 2025)
The colonial archive is marred by a history of violence, particularly in its reductionist and hypersexualized portrayals of Black bodies, especially those of Black women. This problem is rooted in colonialism, racialized misogyny, and the commodification of Black bodies for the entertainment and consumption of dominant cultures. Through exploring scopophilia and different theories of the gaze – imperial, colonial and ethnographic – this thesis uniquely proposes a shift towards an empathetic gaze when considering the representation of Black women in art, given the violence tied to these traditional modes of looking. Drawing inspiration from Tina Campt's A Black Gaze, it advocates for a relational approach that requires the ethical work of care and connotes conscientiousness in looking with and alongside rather than at the Black female body. This research examines the complex dynamics of duty of care, empathy, and the gaze in relation to the representation of Black female body in artworks by Black women artists, within the context of contemporary exhibition spaces. It analyzes the artistic representations of the Black female body in the works of Wangechi Mutu, Tracey Rose, and Lady Skollie, all of whom incorporate images of Sara Baartman – an iconic figure symbolizing the violence, exploitation, and stereotypes endured by African women. The thesis also interrogates the use of three relational schemas associated with the Black female body that shape violent stereotypes: sexuality, the grotesque, and fetishism. Distinctively, this research addresses the paradoxical nature of exhibitionary spaces and questions the responsibilities of viewers when confronted with art that subverts historical representations of the Black female body. Recognising that a number of renowned contemporary Black women artists are utilising the colonial archive to subvert violent stereotypes, this research calls for a multifaceted approach that addresses the complexity and paradoxes in the portrayal of the Black female body, exploring artistic expressions that transcend reductionist and objectifying perspectives to present alternative, empowering, and self-defined narratives.